The development and characterization of a chemical probe targeting PRMT1 over PRMT5. Issue 1 (1st January 2019) - Mann, Sarah A.; Salsburg, Andrew; Causey, Corey P.; Knuckley, Bryan
Graphical abstract: Abstract: Protein arginine methyltransferases (PRMTs) are a family of mammalian enzymes catalyzing the symmetric dimethylation (Type I), asymmetric dimethylation (Type II), or monomethylation (Type III) of arginine residues within proteins. This family is composed of 11 isozymes, however the vast majority of asymmetric and symmetric dimethylation in mammals is completed by either PRMT1 or PRMT5, respectively. In recent years, a number of chemical probes targeting this family of enzymes have been developed, but the majority of these probes lack isozyme specificity. Herein, we report the development of a chemical probe, based on a non-natural peptide sequence, which specifically labels PRMT1 over PRMT5 with high selectivity and sensitivity.